2014
DOI: 10.1111/cge.12456
|View full text |Cite
|
Sign up to set email alerts
|

Genetic epidemiology of tooth agenesis in Japan: a population‐ and family‐based study

Abstract: Tooth agenesis is one of the most common congenital anomalies in humans. However, the etiology of tooth agenesis remains largely unclear, as well as evidence base useful for genetic counseling. Therefore, we estimated the prevalence and sibling recurrence risk, and investigated agenetic patterns systematically. Tooth agenesis was classified into two subtypes: hypodontia (one to five missing teeth) and oligodontia (six or more missing teeth). The prevalence of these two subtypes were 6.8% [95% confidence interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 8 publications
0
14
0
3
Order By: Relevance
“…[1][2][3] Isolated oligodontia can be a heritable developmental abnormality with a 0.1% prevalence. 4 It is often linked to a mutation in genes encoding transcriptional factors involved in early steps of odontogenesis (MSX1, PAX9, AXIN2, IRF6), or components of ectodysplasin signaling (EDA, EDAR, EDARADD) or Wnt signaling pathways (WNT10A, LRP5/6).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Isolated oligodontia can be a heritable developmental abnormality with a 0.1% prevalence. 4 It is often linked to a mutation in genes encoding transcriptional factors involved in early steps of odontogenesis (MSX1, PAX9, AXIN2, IRF6), or components of ectodysplasin signaling (EDA, EDAR, EDARADD) or Wnt signaling pathways (WNT10A, LRP5/6).…”
Section: Introductionmentioning
confidence: 99%
“…Tooth agenesis is classified into two subtypes according to the number of missing teeth: hypodontia (one to five missing teeth, excluding the third molar) and oligodontia (six or more missing teeth, excluding the third molar). Recently, we reported that the prevalences of these two subtypes in the Japanese population are 6.8% (hypodontia) and 0.1% (oligodontia) and that the sibling recurrence risks are 25.0% and 43.8%, respectively, suggesting that the severe phenotype, oligodontia, may be mostly transmitted in a dominant fashion [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interactions involving positive and negative loops among bone morphogenetic protein (BMP), fibroblast growth factors, Sonic hedgehog, and Wnt pathways regulate the morphogenesis of individual teeth (1,4). While the number of teeth is usually strictly controlled in individual species (5), it can increase or decrease congenitally in about 1% of individuals (6)(7)(8). Conditions of decreases and increases in the usual number of teeth are called tooth agenesis and supernumerary teeth, respectively.…”
Section: Introductionmentioning
confidence: 99%